Investigating the mechanical function of the cervix during pregnancy using finite element models derived from high-resolution 3D MRI. Issue 4 (11th March 2016) - Fernandez, M.; House, M.; Jambawalikar, S.; Zork, N.; Vink, J.; Wapner, R.; Myers, K.
Abstract : Preterm birth is a strong contributor to perinatal mortality, and preterm infants that survive are at risk for long-term morbidities. During most of pregnancy, appropriate mechanical function of the cervix is required to maintain the developing fetus in utero. Premature cervical softening and subsequent cervical shortening are hypothesized to cause preterm birth. Presently, there is a lack of understanding of the structural and material factors that influence the mechanical function of the cervix during pregnancy. In this study we build finite element models of the pregnant uterus, cervix, and fetal membrane based on magnetic resonance imagining data in order to examine the mechanical function of the cervix under the physiologic loading conditions of pregnancy. We calculate the mechanical loading state of the cervix for two pregnant patients: 22 weeks gestational age with a normal cervical length and 28 weeks with a short cervix. We investigate the influence of (1) anatomical geometry, (2) cervical material properties, and (3) fetal membrane material properties, including its adhesion properties, on the mechanical loading state of the cervix under physiologically relevant intrauterine pressures. Our study demonstrates that membrane–uterus interaction, cervical material modeling, and membrane mechanical properties are factors that must be deliberately and carefully handled in order to construct a high quality mechanical simulation of pregnancy.